The Analysis of Social Facts in “The Plague” by Albert Camus - Ali, Muhammad Ilham (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This research aims to analyze the social facts and interpret quotes that express them in the novel